Interaction of kazakh and tatar cultures: historical and sociocultural analysis (Journal of history-rus, 2022)
One of the significant scientific directions in the history of Central Asia is the study of the relationship between Kazakhstan and other neighbouring regions. The level of development of relations between countries depends on the positive interaction of cultures. The rich history of human development includes many different vivid cultures with their own unique significance. Cultural evolution is based on a wide range of new worldview positions. The complexity and diversity of cultural systems is formed as a result of their changes based on interaction and transition to a higher quality level. One of the essential components in the study of this process is the awareness of the uniqueness of culture, understanding of the internal and external mechanisms of the social movement of society. The peoples inhabiting the territory of Central Asia have their own unique history; over the millennia, civilizations have formed and flourished here, which have undergone various transformations, experiencing periods of prosperity, decline and stagnation. The further development of this territory, of course, proceeded in the mainstream of world history, changes in the political and socio-economic sphere and the modernization of society entailed new challenges and required solutions and new cultural requests. The events that took place in the late 19th - early 20th centuries demanded the transformation of society, the search for new horizons of human being and consciousness. Over the centuries, the culture of the Kazakh people has also become an integral part of world history. The study of the culture of the traditional Kazakh society shows many aspects of its development were studied fragmentarily, ideological distortions were observed in pre-revolutionary Russian, Soviet and partly foreign historiography. At present, the possibility of studying the Kazakh traditional society with the involvement of new tools of the methodology makes it possible to identify significant aspects of its interaction with neighboring territories. So, in the 19th and early 20th centuries, the city of Kazan became the focus of spiritual life and interaction of peoples living in the Volga region. Kazan as a scientific and cultural center has played a significant role in the history and culture of the Turkic-speaking peoples.The purpose of this study is to consider the interaction of the Kazakh and Tatar cultures and find out the features of the socio-cultural life of the traditional Kazakh society. The authors note that even in the conditions of the loss of statehood, the Kazakhs exchanged cultural experience with neighboring countries.